Nematodes from Achatina fulica Bowdich, 1822 (Mollusca: Gastropoda) in Argentina - Valente, Romina (2016)
The aim of this study is to describe the nematode cysts and larvae found in Achatina fulica, the giant African snail, in the northeast of Argentina. A total of 373 snails were collected from the cities of Puerto Iguazú and Corrientes. Cysts (N= 2958) containing nematodes identified as L3 Strongyluris sp. were found in the mantle cavity of 87 snails from Puerto Iguazú City (Prevalence 23 %; Mean Intensity= 34; Mean Abundance= 8). The shell size correlated with prevalence, mean intensity and mean abundance (p < 0.05) indicating that there is an exposure-infection constant rather than an accidental one. In other hand, the absence of infection in the smallest shell size suggests a threshold of size to be infected. Taking into account that there exist records of A. fulica infected by nematodes of medical and veterinary importance such as Angiostrongylus and Aelurostrongylus in some Brazilian states near Puerto Iguazú, we emphasize the need for snail surveillance.